2018
DOI: 10.1177/1403494817748295
|View full text |Cite
|
Sign up to set email alerts
|

Health and retirement age: Comparison of expectations and actual retirement

Abstract: Aim: We examine the relationship between the subjective assessment of health status and retirement by using information on expected and actual retirement ages. Methods: Subjective data from cross-sectional surveys, conducted in Finland in 2003 and 2008, are linked to information on actual retirement age from register data from 2003 to 2013. Regression models are estimated for actual and expected retirement ages. Results: While the health status is positively correlated with both actual and anticipated full-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The fact that many elderly people are compelled to work due to financial difficulties does not mean that work causes suffering to these individuals. On the contrary, many people feel happy and have positive experiences associated with work, which may lead to greater personal and professional satisfaction, and hence, higher QoL (9) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that many elderly people are compelled to work due to financial difficulties does not mean that work causes suffering to these individuals. On the contrary, many people feel happy and have positive experiences associated with work, which may lead to greater personal and professional satisfaction, and hence, higher QoL (9) .…”
Section: Discussionmentioning
confidence: 99%
“…The non-working elderly had the lowest mean score in the Autonomy facet, since they depend on the retirement pension and/or in support from their families to cover their daily expenses, which reduces their financial independence, and compromises their ability to decide on various aspects related to their daily life, hence resulting in impairment of their QoL (8)(9) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the lower Gross Domestic Product (GDP) per capita countries such as Thailand and Vietnam have a higher life expectancy as compared to Malaysia. The correlation between retirement age and health status jives with Ilmakunnas and Ilmakunnas (2018) regression analysis which concluded that the health status is positively correlated with both actual and anticipated full-time retirement age. 2010 to 2017, the number of tertiary graduates entering the job market has surpassed the number of jobs created for them.…”
Section: Figure 02 Retirement Ages and Life Expectancy In Asean Ciamentioning
confidence: 98%
“…However, the role of health in retirement decisions often receives little attention. Ilmakunnas and Ilmakunnas [22] show in their article Health and retirement age: Comparison of expectations and actual retirement published in this special issue that the relationship between health and retirement decisions is complex. Overall, individuals tend to retire later than they have anticipated.…”
mentioning
confidence: 99%